Electrophoretic Studies on Determination of Stability Constants of Zn(II) and Cd(II) Mixed Complexes (M-Methionine-Cysteine System) - Tiwari, B.B.; Singh, R.K.P.; Kumar, V.; Yadava, K.L. (Asian Journal of Chemistry, 2010)
The stability constant of different complex species of some metal ions viz. Zn2+ and Cd2+ with methionine were determined electrophoretically at an ionic strength 0.1 perchloric acid and 85ºC. The stability constant of complexes M(II)-methionine-cysteine 7.30 and 7.62 (log K values) for Zn(II) and Cd(II) complexes.